An in vitro investigation of species-dependent intestinal transport of selenium and the impact of this process on selenium bioavailability - Thiry, Celine; Ruttens, Ann; Pussemier, Luc; Schneider, Yves-Jacques (British journal of nutrition, 2013)
A range of Se species has been shown to occur in a variety of different foodstuffs. Depending on its speciation, Se is more or less bioavailable to human subjects. In the present study, the role of speciation as a determinant of Se bioavailability was addressed with an investigation of species-specific mechanisms of transport at the intestinal level. The present work focused on four distinct Se compounds (selenate (Se(VI)), selenite (Se(IV)), selenomethionine (SeMet) and methylselenocysteine (MeSeCys)), whose intestinal transport was mimicked through an in vitro bicameral model of enterocyte-like differentiated Caco-2 cells. Efficiency of Se absorption was shown to be species dependent (SeMet>MeSeCys>Se(VI)>Se(IV)). In the case of SeMet, MeSeCys and Se(VI), the highly polarised passage from the apical to basolateral pole indicated that a substantial fraction of transport was transcellular, whilst results for Se(IV) indicated paracellular diffusion. Passage of the organic Se species (SeMet and MeSeCys) became saturated after 3 h, but no such effect was observed for the inorganic species. In addition, SeMet and MeSeCys transport was significantly inhibited by their respective S analogues methionine and methylcysteine, which suggests a common transport system for both kinds of compounds.